String quartet in F minor, op. 95 (parts) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (S. A. Steiner; Austria; Vienna, 2023)
First edition of the parts for the String Quartet in F minor, op. 95, published by S. A. Steiner in Vienna; first issue including the "Musik-Anzeige" for "zwey neue grosse Sinfonien von Ludwig van Beethoven" in the violin part.